Obstacles of Online Learning During the Covid-19 Pandemic Among Science Teachers in Palu City - Rafiqa, Rafiqa; Wahyuni, Sri; Buntu, Amalia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to describe the obstacles to online learning during the COVID-19 pandemic among science teachers in Palu City. This research is a qualitative descriptive study using a survey method which was conducted in person and online. Primary data collection was done by interview, distributing questionnaires totaling 25 questions online to respondents. Respondents were 9 science teachers in 3 junior high schools in Palu Barat sub-district who were more than 25 years old with a bachelor’s degree. The results showed that overall there were 4 items that did not hinder or did not become an obstacle in online learning for teachers, 12 statement items were considered inhibiting by teachers and 9 items were considered very inhibiting by teachers, the difficulty faced by teachers was the difficulty of evaluating practicum activities online, while some subjects in science lessons require practicum activities, this makes the teacher improvise in practicum activities and ask students to do simple independent practicums, but direct practicum is still considered better because the teacher can directly monitor student activities